2003
DOI: 10.1111/j.1538-7836.2003.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of megakaryocytes to synthesize and store a releasable pool of human factor VIII

Abstract: Summary. von Willebrand factor (VWF) is a complex plasma glycoprotein that modulates platelet adhesion at the site of a vascular injury, and it also serves as a carrier protein for factor (F)VIII. As megakaryocytes are the only hematopoietic lineage to naturally synthesize and store VWF within a-granules, this study was performed to determine if expression of a FVIII transgene in megakaryocytes could lead to traf®cking and storage of FVIII with VWF in platelet a-granules. Isolex 1 selected CD34 cells from huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 63 publications
0
60
0
Order By: Relevance
“…FVIII normally circulates in plasma and is not present in platelets or other blood cells (22,23). Our laboratory has previously demonstrated in vitro costorage of FVIII with VWF in megakaryocyte α-granules (22,23) and endothelial Weibel-Palade bodies (21) when FVIII is ectopically expressed in these cells, and VWF enhances this expression. Clinically, 25-30% of hemophilia patients develop inhibitory antibodies in response to FVIII replacement therapy (43,44), and thus gene therapy by constitutive synthesis and release of recombinant FVIII into plasma (i.e., specifying gene therapy to liver or endothelial cells) might not be therapeutic in these patients in the presence of such inhibitory antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FVIII normally circulates in plasma and is not present in platelets or other blood cells (22,23). Our laboratory has previously demonstrated in vitro costorage of FVIII with VWF in megakaryocyte α-granules (22,23) and endothelial Weibel-Palade bodies (21) when FVIII is ectopically expressed in these cells, and VWF enhances this expression. Clinically, 25-30% of hemophilia patients develop inhibitory antibodies in response to FVIII replacement therapy (43,44), and thus gene therapy by constitutive synthesis and release of recombinant FVIII into plasma (i.e., specifying gene therapy to liver or endothelial cells) might not be therapeutic in these patients in the presence of such inhibitory antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This failure may be attributed in part to the fact that none of these approaches directed FVIII synthesis to cells that synthesize and store VWF, even though VWF is known to stabilize FVIII in plasma (40) and in the commercial production of recombinant FVIII products (41,42). FVIII normally circulates in plasma and is not present in platelets or other blood cells (22,23). Our laboratory has previously demonstrated in vitro costorage of FVIII with VWF in megakaryocyte α-granules (22,23) and endothelial Weibel-Palade bodies (21) when FVIII is ectopically expressed in these cells, and VWF enhances this expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,[31][32][33] The advantages of expressing FVIII in platelets are these cells' involvement in early hemostasis and the fact that they serve as a major site for storage of FVIII. 34 In megakaryocytes and endothelial cells the presence of von Willebrand factor should be helpful for stabilizing FVIII. It is possible that FVIII in platelets may not cause the development of neutralizing antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that it may be beneficial to express FVIII in cells that also express its natural carrier protein von Willebrand factor (VWF). [5][6][7][8][9][10][11] In the circulation, VWF protects FVIII from premature clearance and proteolytic degradation by virtue of its ability to bind to it with high affinity. [12][13][14] VWF is expressed in megakaryocytes and vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%